Musculoskeletal injuries and dance exposure across three years in elite adolescent ballet dancers: is there a pattern? - Volkova, V.; Kenny, S. J. (British Journal of Sports Medicine, 2021)
Background Dance is a popular activity among youth at all levels and involves large volumes of training. Reported injury estimates are high in this population, warranting investigation of training volume and injury patterns throughout multiple training years.